Variant Development of the Halal Food Industry In Indonesia: The Role of Sharia Banking - Syahruddin Kadir; Murtiadi Awaluddin; Amiruddin K (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
This research explores the role and contribution of Islamic banking in the halal industry and the development model of the halal food industry. The halal industry's growth with the Indonesian people's lifestyle needs improvement from the perspective of the Islamic finance industry in carrying out financial transaction activities with related parties. Islamic financial industry activities aim to achieve maslahah and prosperity for every consumer or society in general so that the increase in the halal industry is more conservative and competitive with the support from the Islamic banking sector. The research method used is a descriptive qualitative method with a literature review. Based on the results of the analysis, it can be concluded that the development of the halal food industry can be increased through development in the fields of agroindustry, halal logistics, halal lifestyle Islamic boarding schools, exports through MEA, halal food e-commerce, organic halal and halal finance from Islamic banking. The role of Islamic banking is to provide convenience and smoothness for every halal business person, including an e-commerce platform for online transactions, increasing financial literacy for the public, and controlling sources of funds to ensure the production process runs according to halal standards. Islamic banking is one of the supporters of the increase in the halal food industry, both directly and indirectly at home and abroad.